2017
DOI: 10.18632/oncotarget.19075
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligase tripartite motif-containing 71 promotes the proliferation of non-small cell lung cancer through the inhibitor of kappaB-α/nuclear factor kappaB pathway

Abstract: Tripartite motif-containing (TRIM) 71 belongs to the TRIM protein family. Many studies have shown that TRIM71 plays conserved roles in stem cell proliferation, differentiation, and embryonic development; however, the relationship between TRIM71 and tumorigenesis is not clear. In this study, we demonstrate that TRIM71 expression in non-small cell lung cancer (NSCLC) is associated with tumor size, lymph node metastasis, TNM stage, and poor prognosis. We found that TRIM71 was highly expressed in NSCLC cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 35 publications
(22 reference statements)
3
29
0
Order By: Relevance
“…Consistent with our findings, TRIM71 has also been shown to have a tumor suppressive role in lung and colon cancer cells by mediating degradation of LIN28B and consequently upregulating the tumor suppressive microRNA let-7 38,39 . But, it has also been reported that TRIM71 might act as an oncoprotein to activate the NF-κB signaling pathway by degrading IκB-α, or repress the Argonautes-microRNA pathway, leading to development of lung and liver carcinomas 40,41 . These divergent findings may reflect the complexity and heterogeneity of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, TRIM71 has also been shown to have a tumor suppressive role in lung and colon cancer cells by mediating degradation of LIN28B and consequently upregulating the tumor suppressive microRNA let-7 38,39 . But, it has also been reported that TRIM71 might act as an oncoprotein to activate the NF-κB signaling pathway by degrading IκB-α, or repress the Argonautes-microRNA pathway, leading to development of lung and liver carcinomas 40,41 . These divergent findings may reflect the complexity and heterogeneity of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Other TRIMs, although do not exert a specific role in the regulation of cell cycle phase transitions, are yet involved in controlling carcinogenesis and cancer progression (Table 1). Most of these TRIMs, like TRIM11 [70,71,72,73,74], TRIM23 [75], TRIM24 [76], TRIM25 [77,78,79], TRIM31 [80], TRIM37 [81], TRIM47 [82,83], TRIM65 [84], and TRIM71 [85] are up-regulated in cancer cells and tissues, playing an oncogenic role in different types of cancer. These TRIMs are often associated with unfavorable prognosis and promote cancer cells proliferation and migration, being often associated with proteins of central signaling pathways.…”
Section: Trims and Cell Cycle Progressionmentioning
confidence: 99%
“…Tripartite motif (TRIM) family proteins are considered as a kind of E3 ubiquitin ligase, with more than 80 members identified in humans to date [ 10 ]. They exert diverse biological functions in human, such as cell proliferation, apoptosis, invasion, innate immunity, and autophagy [ 11 15 ]. TRIM52 is a novel TRIM family protein.…”
Section: Introductionmentioning
confidence: 99%